PENGGUNAAN MODEL PEMBELAJARAN LANGSUNG SEBAGAI STRATEGI MENGAJAR MUSIKALISASI PUISI [The Use of Direct Learning Models as a Strategy to Teach Musical Poetry] - sakila sakila (Kantor Bahasa Provinsi Maluku, 2018)
Writing this scientific article examines the use of direct learning models as a musical learning strategy for poetry. The purpose of this paper is to describe the use of direct learning models as a musical learning strategy for poetry. The data collection process is carried out using the literature study method. The collected data is selected and sorted according to the study topic. Then the preparation of the paper is based on data that has been prepared logically and systematically. Data analysis techniques are descriptive argumentative. The formulation of the problem contained in this paper is how to use direct learning methods as a musical learning strategy for poetry. Based on data analysis, it was concluded that using direct learning models can improve students' ability in learning poetry musicization. Based on this, it is recommended that teachers can apply direct learning models to improve students' ability in learning poetry musicilization.Penulisan artikel ilmiah ini mengkaji tentang penggunaan model pembelajaran langsung sebagai strategi pembelajaran musikalisasi puisi. Tujuan penulisan ini adalah untuk mendeskripsikan penggunaan model pembelajaran langsung sebagai strategi pembelajaran musikalisasi puisi. Proses pengumpulan data dilakukan dengan metode studi kepustakaan. Data yang terkumpul diseleksi dan diurutkan sesuai dengan topik kajian. Kemudian dilakukan penyusunan karya tulis berdasarkan data yang telah dipersiapkan secara logis dan sistematis. Teknik analisis data bersifat deskriptif-argumentatif. Rumusan masalah yang terdapat pada tulisan ini adalah bagaimanakah penggunaan metode pembelajaran langsung sebagai strategi pembelajaran musikalisasi puisi. Berdasarkan analisis data disimpulkan bahwa dengan menggunakan model pembelajaran langsung dapat meningkatkan kemampuan siswa dalam pembelajaran musikalisasi puisi. Berdasarkan hal tersebut, disarankan agar guru dapat menerapkan model pembelajaran langsung untuk meningkatkan kemampuan siswa dalam pembelajaran musikalisasi puisi.